Effects of achievement goals on female aesthetic athletes` disordered eating attitudes - Scoffier, S.; Corrion, K.; d`Arripe-Longueville, F. (Science & Sports, 2013)
Objective: This study examined how achievement goals are related to athletes` eating disorders. Method: The sample consisted of 196 female adolescents involved in aesthetic sports at an elite level. Data were examined through structural equation modeling. Results: The data showed that performance-avoidance goals were negatively related to eating disorders, whereas both performance-approach and mastery-avoidance goals positively predicted these disorders. These findings indicate that performance-approach and mastery-avoidance goals may be risk factors for the development of eating disorders, whereas performance-avoidance goals may have protective effects.